The hypothalamo-neurohypophyseal system: from genome to physiology - Murphy, David; Grinevich, Valéry (Journal of neuroendocrinology, 2012)
The elucidation of the genomes of a large number of mammalian species has produced a huge amount of data on which to base physiological studies. These endeavours have also produced surprises, not least of which has been the revelation that the number of protein coding genes needed to make a mammal is only 22,333 (give or take). However, this small number belies an unanticipated complexity that has only recently been revealed thanks to genomic studies. This complexity is evident at a number of levels: (1) cis-regulatory sequences; (2) non-coding and anti-sense mRNAs, most of which have no known function; (3) alternative splicing that results in the generation of multiple, subtly different mature mRNAs from the precursor transcript encoded by a single gene; (4) post-translational processing and modification. In this review, we examine the steps being taken to decipher genome complexity in the context of gene expression, regulation and function in the hypothalamo-neurohypophyseal system (HNS). Five unique stories explain: (1) the use of transcriptomics to identify genes involved in the response to physiological (dehydration) and pathological (hypertension) cues; 2) the use of mass spectrometry for single-cell level identification of biological active peptides in the HNS, and to measure in vitro release; (3) the use of transgenic lines that express fusion transgenes that enable (by cross-breeding) the generation of double transgenic lines that can be used to study vasopressin (AVP) and oxytocin (OXT) neurones in the HNS, their neuroanatomy, electrophysiology, and activation upon exposure to any given stimulus; (4) the use of viral vectors to demonstrate that somato-dendritically released AVP plays an important role in cardiovascular homeostasis by binding to V1a receptors on local somata and dendrites; and (5) the use of virally-mediated optogenetics to dissect the role of OXT and AVP in the modulation of a wide variety of behaviours.
Gesehen am 29.10.2018
Author manuscript available in PMC 2013 Apr 1